Probing the role of metal ions on reversible peptide–protein interactions by NMR. Issue 2 (2004) - D'Amelio D'Amelio, Nicola Nicola; Gaggelli Gaggelli, Elena Elena; Gaggelli Gaggelli, Nicola Nicola; Mancini Mancini, Francesca Francesca; Molteni Molteni, Elena Elena; Valensin Valensin, Daniela Daniela; Valensin Valensin, Gianni Gianni
Abstract : This work provides evidence that paramagnetic lanthanide ions constitute ideal probes suitable for investigations of metal effects upon peptide–receptor interactions with the use of NMR methods. Cerium(III) is herein used for assessing metal effects upon the interaction between angiotensin II and a fragment from the AT1A receptor. Angiotensin II forms a complex with cerium(III) in water while the fCT 300–320 receptor fragment is poorly affected by cerium(III). However, the addition of the fragment displaces cerium(III) from the complex, thus directly demonstrating the higher affinity of angiotensin II for the receptor and probing the peptide residues involved in receptor binding.